Stability of the tomato to black bacterial blight (xanthomonas vesicatoria Dowson) - Лысак, С. А.; Лысак, З. В. (Scientific Progress & Innovations, 2012)
Research of 2008–2011 resistance of tomato original material to black bacterial blight is considered in the article. Studied of 579 collection samples of a tomato of a different ecological and geographical origin. The collection material is differentiated on level of polygene stability to black bacterial blight (Xanthomonas vesicatoria Dowson). The steady samples allocated to given illness and standards differentiator are recommended for using in selection work to the given sign.